2021
DOI: 10.3325/cmj.2021.62.376
|View full text |Cite
|
Sign up to set email alerts
|

The vicious interplay between disrupted sleep and malignant brain tumors: a narrative review

Abstract: Malignant brain tumors are among the most aggressive human neoplasms. One of the most common and severe symptoms that patients with these malignancies experience is sleep disruption. Disrupted sleep is known to have significant systemic pro-tumor effects, both in patients with other types of cancer and those with malignant brain lesions. We therefore provide a review of the current knowledge on disrupted sleep in malignant diseases, with an emphasis on malignant brain tumors. More specifically, we review the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 102 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…According to the data from the health and retirement study in the United States, insomnia symptoms, both cumulatively and individually, are associated with incident HF ( 23 ). Sleep loss is also related to various kinds of cancer, such as neck and head cancer ( 24 ), prostate cancer ( 25 ), and malignant brain tumor ( 26 ). Michael et al reported that sleep loss might activate spontaneous cellular innate immunity ( 27 ).…”
Section: Active Exposurementioning
confidence: 99%
“…According to the data from the health and retirement study in the United States, insomnia symptoms, both cumulatively and individually, are associated with incident HF ( 23 ). Sleep loss is also related to various kinds of cancer, such as neck and head cancer ( 24 ), prostate cancer ( 25 ), and malignant brain tumor ( 26 ). Michael et al reported that sleep loss might activate spontaneous cellular innate immunity ( 27 ).…”
Section: Active Exposurementioning
confidence: 99%